2022
DOI: 10.3389/fmicb.2022.777986
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Cultivable Bacterial Fraction of Sediments From the Red Sea Mangroves and Physiological, Chemotaxonomic, and Genomic Characterization of Mangrovibacillus cuniculi gen. nov., sp. nov., a Novel Member of the Bacillaceae Family

Abstract: Mangrove forests are dynamic and productive ecosystems rich in microbial diversity; it has been estimated that microbial cells in the mangrove sediments constitute up to 91% of the total living biomass of these ecosystems. Despite in this ecosystem many of the ecological functions and services are supported and/or carried out by microorganisms (e.g., nutrient cycling and eukaryotic-host adaptation), their diversity and function are overlooked and poorly explored, especially for the oligotrophic mangrove of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…This kind of ‘black box’ approach (Dance, 2020) is based on manipulative experiments (in vitro, e.g., microcosm enrichments; Caracciolo et al, 2013; Kamran et al, 2020) and innovative isolation technologies (in situ and ex situ, e.g., diffusion chambers and microbial traps; Berdy et al, 2017; Jaswal et al, 2019). Coupled with molecular techniques, microbial ‘fishing’ has successfully unveiled the existence and role of specific microbial strains and consortia in a variety of complex environments, including the discovery of novel strains from mangrove ecosystems and the formation of siderite in marine sediment (Iino et al, 2007; Kamran et al, 2020; Schmidt & Scow, 1997; Sefrji, Marasco, et al, 2021; Sefrji, Michoud, et al, 2021; Sefrji et al, 2022). According to this premise, we raise the following questions, addressing them to the concerned scientific community: Can microbial ‘fishing’ lead us to discover novel key players in micritization?…”
Section: Lessons From the Studies On The ‘Microbial Dark Matter’mentioning
confidence: 99%
“…This kind of ‘black box’ approach (Dance, 2020) is based on manipulative experiments (in vitro, e.g., microcosm enrichments; Caracciolo et al, 2013; Kamran et al, 2020) and innovative isolation technologies (in situ and ex situ, e.g., diffusion chambers and microbial traps; Berdy et al, 2017; Jaswal et al, 2019). Coupled with molecular techniques, microbial ‘fishing’ has successfully unveiled the existence and role of specific microbial strains and consortia in a variety of complex environments, including the discovery of novel strains from mangrove ecosystems and the formation of siderite in marine sediment (Iino et al, 2007; Kamran et al, 2020; Schmidt & Scow, 1997; Sefrji, Marasco, et al, 2021; Sefrji, Michoud, et al, 2021; Sefrji et al, 2022). According to this premise, we raise the following questions, addressing them to the concerned scientific community: Can microbial ‘fishing’ lead us to discover novel key players in micritization?…”
Section: Lessons From the Studies On The ‘Microbial Dark Matter’mentioning
confidence: 99%
“…Since then, advances in molecular techniques have allowed the further discovery of the diversity and functions of the mangrove sediment microbiome. New microorganisms (among others, Sefrji et al, 2021 , 2022 ) and microbial roles in nutrient cycling have been recognized to determine profound effects (Volland et al, 2022 ), which will be reviewed here, on sediment microbial communities and overall ecosystem functioning. In this review, we first introduce the main groups of bioturbating macrofaunal species and their ecology and then, reviewing the more recent literature, explore the diversity, dynamics and function of the sediment microbiome considering the impact of animal bioturbation, particularly the ‘halo effect’, as well as the effect of other ecosystem engineers, namely plant roots, on reconditioning of sediments.…”
Section: Aim Of the Reviewmentioning
confidence: 99%
“…New technologies for studying the culturable and the whole microbiome of mangrove sediment and the other compartments of the ecosystem suggest that many microorganisms are yet to be discovered and may represent potentially invaluable resources for the sustainability of tropical coastal ecosystems (Allard et al, 2020 ; Demain & Vaishnav, 2011 ; Sefrji et al, 2022 ). For example, three novel bacteria have been isolated from bioturbated sediments from arid mangroves of the central Red Sea: Kaustia mangrove (Sefrji et al, 2021 ), Mangrovibacillus cuniculi (Sefrji et al, 2022 ) and Mangrovivirga cuniculi (Sefrji et al, 2022 ).…”
Section: The Mangrove Microbiome As Natural Capital To Be Leveraged B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some are complex, such as the need for specific growth signals ( Bruns et al, 2002 ; Nichols et al, 2008 ), dependence on other microorganisms ( D’Onofrio et al, 2010 ; He et al, 2015 ), development as microcolonies ( Davis et al, 2011 ) and absence of suitable electron acceptors and/or essential nutrients ( Köpke et al, 2005 ), while others are simpler to address, such as an insufficient incubation periods ( Janssen et al, 2002 ; Davis et al, 2005 ), and the control of fast-growing species that can overcome those with slower growth ( Kato et al, 2018 ). Several studies over the past years have shown that it is possible to isolate previously uncultivated microorganisms by using innovative strategies and approaches, such as low nutrient concentrations and longer incubation times ( Janssen et al, 2002 ; Davis et al, 2005 ; Pulschen et al, 2017 ; Sefrji et al, 2021a , b , 2022 ). Moreover, cultivation success can be improved using whole metagenome analysis to unravel microorganism key metabolic pathways that can inspire new cultivation strategies ( Hedlund et al, 2014 ; Cross et al, 2019 ), as well as by understanding the trophic interactions occurring within the overall microbial community ( Zamkovaya et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%